Analisis Hermeneutik Terhadap Kualifikasi Kepemimpinan Musa dalam Membentuk Team Work Berdasarkan Keluaran 18:21 - Amita Prissila; Frans Aliadi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
This study aims to analyze the leadership qualifications of Moses in Exodus 18:21 and examine their relevance for contemporary Christian team leadership. The research is grounded in the increasing complexity of modern leadership challenges, which often prioritize structural effectiveness without sufficient ethical and spiritual foundations. Employing a qualitative approach with a historical-grammatical hermeneutical method, this study interprets the text within its historical, literary, and lexical contexts. The findings reveal that the four leadership criteria—capable, God-fearing, trustworthy, and hating dishonest gain—form an integrated value system that undergirds Israel’s collective leadership structure. The novelty of this research lies in its interpretation of Exodus 18:21 not merely as a description of Moses’ personal charisma, but as a paradigm for participatory and ethically grounded team leadership. Theologically, the “fear of God” functions as the normative center that integrates competence and integrity. These findings suggest that contemporary Christian leadership development should prioritize spiritual character and moral accountability as foundational elements in building sustainable and integrity-based teamwork..